Perancangan Mesin Perontok Padi Dengan Sistem Rotari - Pristiansyah, Pristiansyah; Hasdiansah, Hasdiansah; Rohman, Habibu; Saputra, Rahman; Aprilia, Silvy (Politeknik Negeri Padang, 2025)
Rice is one of the staple foods consumed by the people of Indonesia, including the Bangka Belitung Islands Province, more precisely in Bangka Regency, Riau Silip District, Banyu Asin Village. Newly harvested rice is usually not yet separated from the straw/panicle. The rice harvesting process still uses traditional tools or also called gebotan. One example is the rice threshing machine in Banyu Asin Village which has not been able to maximize the threshing results, which results in a long threshing process. The machine is only capable of threshing 30 kg/hour of rice that is put into the machine. Based on these needs, a rice threshing machine design was made to facilitate the threshing process. The design of the rice threshing machine refers to the design method, namely: planning, conceptualizing, designing, and finishing, then assessed based on technical and economic aspects. The designed machine uses a rotary system to thresh rice from its stalks, uses a combustion engine as a driving system, pulleys and belts as transmission elements, and the machine can be moved because it is lighter than existing machines. From the design results, this rice threshing machine has a minimum capacity of 80 kg/hour.